2014
DOI: 10.1016/j.electstud.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Who's favored by evaluative voting? An experiment conducted during the 2012 French presidential election

Abstract: Under evaluative voting, the voter freely grades each candidate on a numerical scale, with the winning candidate being determined by the sum of the grades they receive. This paper compares evaluative voting with the two-round system, reporting on an experiment which used various evaluation scales, conducted during the first round of the 2012 French presidential election. Invitations to participate in the study were extended to around 5,000 voters in three cities, and the experiment attracted 2,340 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…Each participant tested two alternative rules for deciding on the ten candidates in this election: approval voting and a variant of evaluative voting. We refer the reader to Baujard et al (2013) for a complete presentation of the protocol, and to Grofman et al (2011) for more details of the in situ methodology. 4 The experiment was performed in five polling stations.…”
Section: Design Of the Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each participant tested two alternative rules for deciding on the ten candidates in this election: approval voting and a variant of evaluative voting. We refer the reader to Baujard et al (2013) for a complete presentation of the protocol, and to Grofman et al (2011) for more details of the in situ methodology. 4 The experiment was performed in five polling stations.…”
Section: Design Of the Experimentsmentioning
confidence: 99%
“…Baujard et al (2014) showed that candidates fall into three categories according to how they are perceived by the electorate.…”
Section: Candidate-specific Label Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it is more likely strategyproof than BMC or any other form of voting based on the summation or the average of grades. Indeed, it generalizes the approval voting, one of the most valued functions according to many specialists in Social Choice Theory (see [19,20,21]). …”
Section: Discussionmentioning
confidence: 99%